Seasonality of the bacterial and archaeal community composition of the Northern Barents Sea - Thiele, Stefan; Vader, Anna; Thomson, Stuart; Saubrekka, Karoline; Petelenz, Elzbieta; Müller, Oliver; Bratbak, Gunnar; Øvreås, Lise (Frontiers in Microbiology, 2023)
The Barents Sea is a transition zone between the Atlantic and the Arctic Ocean. The ecosystem in this region is highly variable and a seasonal baseline of biological factors is needed to monitor the effects of global warming. Here, we report the results from the investigations of the bacterial and archaeal community in late winter, spring, summer, and early winter along a transect through the northern Barents Sea into the Arctic Ocean east of Svalbard using 16S rRNA metabarcoding. Winter samples were dominated by members of the SAR11 clade and a community of nitrifiers, namely Cand. Nitrosopumilus and LS-NOB (Nitrospinia), suggesting a prevalence of chemoautotrophic metabolisms. During spring and summer members of the Gammaproteobacteria (mainly members of the SAR92 and OM60(NOR5) clades, Nitrincolaceae) and Bacteroidia (mainly Polaribacter, Formosa, and members of the NS9 marine group), which followed a succession based on their utilization of different phytoplankton derived carbon sources, prevailed. Our results indicate that Arctic marine bacterial and archaeal communities switch from carbon cycling in spring and summer to nitrogen cycling in winter and provide a seasonal baseline to study the changes of these processes in response to the effects of climate change.